Antimicrobial Activity of Extracts of Acanthus ilicifolius Extracted from the Mangroves of Karwar Coast Karnataka - and J.L. Rathod, Pradeep V. Khajure* (Recent Research in Science and Technology, 2010)
Abstract The antimicrobial activity of n-hexane, chloroform and methanol extracts of leaves and roots of the plant Acanthus ilicifolius were studied. Ampicillin and clotrimazole were used as standard antibacterial and antifungal agents respectively. The result of the study revealed that the n-hexane extract and chloroform extract of leaves exhibited strong inhibitory action against Bacillus subtilis, Staphylococcus aureus, Candida albicans, Aspergillus fumigatus and Aspergillus niger and moderate inhibitory action against Pseudomonas aeruginosa and Proteus vulgaris. The rest of the extracts showed good inhibitory activity. Keywords: Acanthus ilicifolius, Agar disc diffusion method, Mangrove forest antimicrobial activity.